Economics of public WiFi - Potts, Jason (Journal of Telecommunications and the Digital Economy, 2014)
Local governments in urban regions continue to find the idea of public or municipal WiFi attractive. This is for multiple reasons, not all of which are based on economic logic (such as city branding, vote-buying, emergency services, commercial lobbying, peak-traffic broadband off-loading). However, the purpose of this paper is to gather together the basic economic arguments for and against public provision of municipal WiFi. First, we consider what type of economic good WiFi is, and the logic for public rather than market provision. Second, we review four main economic arguments against public WiFi (capitalization; no market failure; competitive distortion; inefficiency of supply side response). Finally, we consider what may be the strongest, yet least made, case for publicly funded municipal WiFi, which is local demand discovery as an implicit subsidy for WiFi entrepreneurship and innovation.